Therapeutic efficacy of jeoryeong-tang in dextran sulfate sodium-induced mouse model of inflammatory bowel disease - Il-Woong Jang; Seung Mok Ryu; Do-Hyun Kim; Sun-Young Hwang; Kwanhwan Wi; Soong-In Lee; Mee-Hyun Lee (Journal of Traditional and Complementary Medicine)
Background: Jeoryeong-tang (JRT) was first recorded in Shanghanlun. It is composed of Polyporus Sclerotium, Poria, Asini Corii Colla, Alisma Rhizome, and Talcum at the same weight ratio. These medicinal materials are known for diuretic and hemostatic effects and have been traditionally used to treat kidney and bladder diseases. However, their potential therapeutic effects on colon diseases, particularly inflammatory bowel disease (IBD), have not been extensively studied. Therefore, this study aimed to investigate the therapeutic efficacy of JRT in IBD and explore its underlying anti-inflammatory mechanisms using a murine model of colitis induced by dextran sulfate sodium (DSS). Methods: Mice were treated with 3.0 % or 2.5 % DSS for 6 days to induce colitis and JRT extract was then administered at a low level of 40 mg/kg (JRT-L), a medium level of 120 mg/kg (JRT-M), or a high level of 400 mg/kg (JRT-H) once a day. During the administration period, clinical disease activity index (DAI) reflecting survival rate, diarrhea, bloody stool, and weight loss rate was evaluated. The degree of colonic tissue damage was scored and evaluated through hematoxylin and eosin staining. Cyclooxygenase-2 (COX-2), p-STAT3 and p-ERK expression were examined with immunohistochemistry. Tumor necrosis factor-α (TNF-α), interleukin (IL)-6 and -1β levels were analyzed using a cytokine enzyme-linked immunosorbent assay. Results: Among mice treated with 3.0 % DSS, JRT-M significantly improved the survival rate compared to other treatments as a result of observation for a total of 14 days. While, in the 2.5 % DSS-treated model, the average body weights of mice in both of JRT-M and JRT-H groups were significantly higher than that in the DSS group. In addition, the JRT-M group showed significantly lower DAI score than that in the DSS group. As a result of evaluating the extent of colon tissue damage, JRT-M and JRT-H groups both showed significantly lower inflammatory index and thinner muscular externa thickness than the DSS group. The expression of COX-2, p-STAT3 and p-ERK in colon tissue were significantly suppressed in JRT-M and JRT-H groups compared to that in the DSS group. Moreover, serum TNF-α was significantly suppressed in the JRT-H group compared to that in the DSS group. Conclusions: Jeoryeong-tang has a promising therapeutic potential for treating IBD through its anti-inflammatory properties. Findings of this study suggest that JRT could be a valuable candidate for further clinical investigations in the treatment of IBD.